Odpowiedzi

Najlepsza Odpowiedź!
2010-03-24T22:16:48+01:00
12
√32+√72-√50=4√2+6√2-5√2=5√2
√80-√125+√500=4√5-5√5+10√5=9√5
√242-√300+√338-√48=11√2-10√3+13√2-4√3=24√2-14√3
√12+√75+√24+√96=2√3+5√3+2√6+4√6=7√3+6√6
√12+√243-√108=2√3+9√3-6√3=5√3
√28-√175+√252=2√7-5√7+6√7=3√7
√800+√80-√200+√500=20√2+4√5-10√2+10√5=10√2+14√5
√392-√150+√578-√486=14√2-5√6+17√2-9√6=31√2-14√6

13
2+4√5/2=1+2√5
6-3√2/3=2-√2
-4+3√28/8=-4+6√7/8=-1/2+3/4 √7
-(2+√8/2)=-1-√2
-(5-2√50/5)=-1+2√2
√12-2√27/√3=√4-2√9=2-6=-4
√8-4/√2-2=2√2-4/√2-2=2
5+√6/√24+10=5+√6/2√6+10=1/2

14
a √12-2√3=0 W
5-2√5+2√5=5 W
2√2-3-3-2√2=-6W
3-4√3 NW
-10√3+3√3+4√3=-3√3 NW
3√2(√3-1)/√3-1=3√2 NW
√5-1-√5=-1 W
2√5-1+1=2√5 NW

15
10∛2-6∛2+∛2=5∛2
5∛3+4∛3+3∛4=12∛3
⁴√2-2⁴√2+3⁴√2=2⁴√2
⁴√3+2⁴√3-3⁴√3=0
-10+6∛3+5∛2
2-2⁴√2-2⁴√2=2
√6√81*2*16*2 *3∛2 -2⁶√2=√3*2*9*4*2*3∛2 -2⁶√2=36⁶√2 -2⁶√2=34⁶√2
∛5*2*2√2*5√2*5*2 +∛-2=10∛2-∛2=9∛2

16
√9(16+4+5)=3*5=15
√25(9+14+2)=5*5=25
√27(2+9+16)=3*3=9
√64(15+3+9)=4*3=12
√11²(3²+4²)=11*5=55
√15²(3²+4²)=15*5=75
√12²(5²-4²)=12*3=36
√11²(9²+6²+2²)=11*11=121

1
a)3x+2y
b)
2(a+1/2b)
2010-03-24T22:39:00+01:00
12
a)√32+√72-√50=4√2+6√2-5√2=5√2

b)√80-√125+√500=4√5-5√5+10√5=9√5

c)√242-√300+√338-√48=11√2-10√3+13√2-4√3=24√2-14√3

d)√12+√75+√24+√96=2√3+5√3+2√6+4√6=7√3+6√6

e)√12+√243-√108=2√3+9√3-6√3=5√3

f)√28-√175+√252=2√7-5√7+6√7=3√7

g)√800+√80-√200+√500=20√2+4√5-10√2+10√5=10√2+14√5

h)√392-√150+√578-√486=14√2-5√6+17√2-9√6=31√2-14√6
...................................................................
13
a)2+4√5/2=1+2√5

b)6-3√2/3=2-√2

c)-4+3√28/8=-4+6√7/8=-1/2+3/4 √7

d)-(2+√8/2)=-1-√2

e)-(5-2√50/5)=-1+2√2

f)√12-2√27/√3=√4-2√9=2-6=-4

g)√8-4/√2-2=2√2-4/√2-2=2

h)5+√6/√24+10=5+√6/2√6+10=1/2
.......................................................
14
a) a √12-2√3=0 W
b) 5-2√5+2√5=5 W
c) 2√2-3-3-2√2=-6W
d)3-4√3 NW
e)-10√3+3√3+4√3=-3√3 NW
f) 3√2(√3-1)/√3-1=3√2 NW
g)√5-1-√5=-1 W
h) 2√5-1+1=2√5 NW
......................................................
15
a)10∛2-6∛2+∛2=5∛2

b)5∛3+4∛3+3∛4=12∛3

c)⁴√2-2⁴√2+3⁴√2=2⁴√2

d)⁴√3+2⁴√3-3⁴√3=0

e)-10+6∛3+5∛2

f)2-2⁴√2-2⁴√2=2

g)√6√81*2*16*2 *3∛2 -2⁶√2=√3*2*9*4*2*3∛2 -2⁶√2=36⁶√2 -2⁶√2=34⁶√2

h)∛5*2*2√2*5√2*5*2 +∛-2=10∛2-∛2=9∛2
...........................................................................
16
a) √9(16+4+5)=3*5=15

b)√25(9+14+2)=5*5=25

c)√27(2+9+16)=3*3=9

d)√64(15+3+9)=4*3=12

e)√11²(3²+4²)=11*5=55

f)√15²(3²+4²)=15*5=75

g)√12²(5²-4²)=12*3=36

h)√11²(9²+6²+2²)=11*11=121

pozdrawiam;)